Evaluation of Campus Sustainability in Teacher Education Institutes of Pakistan - Hameed, Gulnaz; Khan, Sehrish; Rehman, Ayesha; Iqbal, Javaid; Ali Shams, Haider (2023)
Since the approval of Agenda 2030, higher education institutions (HEIs) have expressed increasing apprehension regarding sustainability matters. However, this does not satisfy societal constituents who are committed to innovation and excellence. All United Nations Member States endorsed the 17 Sustainable Development Goals (SDGs) in 2015 as a universal call to action; they present a challenge for higher education institutions (HEIs) in terms of evaluating their performance and the endeavours required to achieve them. Nevertheless, the metric management system that higher education institutions (HEIs) swiftly adopted gave rise to rankings that contrast HEIs based on metrics unrelated to the sustainability aspects of the seventeen SDGs.